2012
DOI: 10.5402/2012/597876
|View full text |Cite
|
Sign up to set email alerts
|

Focus on ADF/Cofilin: Beyond Actin Cytoskeletal Regulation

Abstract: Actin depolymerizing factor (ADF)/cofilin, an actin binding protein ubiquitously expressed in a variety of organisms, is required for regulation of actin dynamics. The activity of ADF/cofilin is dependent on serine 3 phosphorylation by LIM kinase (LIMK), which is regulated by the Rho small GTPase signaling pathway. ADF/cofilin is strongly associated with several important cell biological functions, including cell cycle, morphological maintenance and locomotion. These functions affect several biological events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
(116 reference statements)
0
2
1
Order By: Relevance
“…Cofilin 1 promoted proliferation and decreased apoptosis in T24 and RT4 cells. Furthermore, Cofilin 1 overexpression promoted cell cycle progression, while Cofilin 1 knockdown resulted in G1 phase arrest, which confirmed that Cofilin 1 promoted cell proliferation; however, this result contradicts previous results regarding the effects of Cofilin 1 on the cell cycle [ 33 , 34 ]. Cofilin 1 enhanced the migration and invasion capacities of T24 and RT4 cells, indicating that Cofilin 1 contributes to invasion and metastasis in bladder tumors as well as in mammary tumors [ 13 , 17 , 35 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Cofilin 1 promoted proliferation and decreased apoptosis in T24 and RT4 cells. Furthermore, Cofilin 1 overexpression promoted cell cycle progression, while Cofilin 1 knockdown resulted in G1 phase arrest, which confirmed that Cofilin 1 promoted cell proliferation; however, this result contradicts previous results regarding the effects of Cofilin 1 on the cell cycle [ 33 , 34 ]. Cofilin 1 enhanced the migration and invasion capacities of T24 and RT4 cells, indicating that Cofilin 1 contributes to invasion and metastasis in bladder tumors as well as in mammary tumors [ 13 , 17 , 35 ].…”
Section: Discussioncontrasting
confidence: 56%
“…It was also revealed that DSGOST inhibits RhoA-mediated pathways for the phosphorylation of cofilin and MLC in coldand ET-1-exposed vascular cells, indicating that DSGOST may suppress contraction of vascular cells via regulation of actin reorganization (30)(31)(32)(33). Based on DSGOST inhibition of either RhoA activation or cytoskeletal reorganization, it is hypothesized that DSGOST may be useful in the management of other diseases with dysregulation of actin cytoskeleton in vascular cells.…”
Section: Discussionmentioning
confidence: 99%
“…These sustain the balance of actin polymerization and depolymerization and therefore are strongly controlled in their expression and activity pattern [ 16 ],[ 18 ],[ 21 ]. Here, the actin regulatory protein, actin depolymerization factor (ADF)/cofilin acts as a key player by severing filaments [ 22 ]. ADF/cofilin becomes inactive when it is phosphorylated at its serine 3 residue.…”
Section: Introductionmentioning
confidence: 99%